2014
DOI: 10.1016/j.jadohealth.2014.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Age at Time of Receipt of One or More Sexual Risk Reduction Interventions

Abstract: Purpose Age of the target audience at time of intervention is thought to be a critical variable influencing the effectiveness of adolescent sexual risk reduction interventions. Despite this postulated importance, to date studies have not been designed to enable a direct comparison of outcomes according to age at time of intervention delivery. Methods We examined outcomes of 598 youth who were sequentially involved in two randomized controlled trials of sexual risk prevention interventions, the first one deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…As previously reported [18,19], at baseline in grade-10, prior to receipt of either BFOOY or HFLE, those youth who had attended schools receiving FOYC in grade-6 (N=530) exhibited higher condom-use skills, HIV/AIDS knowledge, and condom-use self-efficacy than youth in schools not receiving FOYC (N=1579). In terms of improvements in HIV-prevention skills, youth who had not been exposed to FOYC in grade-6 demonstrated greater positive change as a result of receipt of BFOOY.…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…As previously reported [18,19], at baseline in grade-10, prior to receipt of either BFOOY or HFLE, those youth who had attended schools receiving FOYC in grade-6 (N=530) exhibited higher condom-use skills, HIV/AIDS knowledge, and condom-use self-efficacy than youth in schools not receiving FOYC (N=1579). In terms of improvements in HIV-prevention skills, youth who had not been exposed to FOYC in grade-6 demonstrated greater positive change as a result of receipt of BFOOY.…”
Section: Resultssupporting
confidence: 59%
“…Males exhibited significantly higher condom-use skills and condom-use self-efficacy and females show higher HIV/AIDS knowledge. For all youth, condom-use skills, HIV/AIDS knowledge, condom-use self-efficacy, and condom-use intention displayed significant increases with time [18, 19]. Significant main effects for intervention showed that compared to youth who received both FOYC and BFOOY, WW+BFOOY had significantly lower condom use skills, HIV/AIDS knowledge, condom use self-efficacy and intention and WW+HFLE had lower HIV/AIDS knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Results at six, 12 and 18 months follow-up described elsewhere (Dinaj-Koci et al, 2014; Stanton et al, submitted) indicate that BFOOY is an effective sexual risk-reduction intervention. This present analyses offer the unique opportunity to examine whether (and if so how) a brief parent-adolescent sexual risk communication intervention in addition to an effective adolescent intervention would confer added benefit among older adolescents who are gradually engaging in more risky behaviors.…”
Section: Introductionmentioning
confidence: 67%